Immigrant Employment and Earnings Growth in Canada and the U.S.: Evidence from Longitudinal Data - Neeraj Kaushal; Yao Lu; Nicole Denier; Julia Shu-Huah Wang; Stephen Trejo (Institute for the Study of Labor (IZA), 2015)
We study the short-term trajectories of employment, hours worked, and real wages of immigrants in Canada and the U.S. using nationally representative longitudinal datasets covering 1996-2008. Models with person fixed effects show that on average immigrant men in Canada do not experience any relative growth in these three outcomes compared to men born in Canada. Immigrant men in the U.S., on the other hand, experience positive annual growth in all three domains relative to U.S. born men. This difference is largely on account of low-educated immigrant men, who experience faster or longer periods of relative growth in employment and wages in the U.S. than in Canada. We further compare longitudinal and cross-sectional trajectories and find that the latter over-estimate wage growth of earlier arrivals, presumably reflecting selective return migration.
Keywords: J15; J3; J18; 330; U.S. immigrants; Canadian immigrants; economic assimilation; longitudinal data; immigration; employment; wages; comparative study